Serine Protease 27, a Prognostic Biomarker in Pan-cancer and Associated with the Aggressive Progression of Breast Cancer - Xu, Yiying; Shen, Yanyan; Bhandari, Adheesh; Hirachan, Suzita; Wang, Ouchen; Xia, Erjie (Current Medicinal Chemistry, 2024)
Background: To create effective medicines, researchers must first identify the common or unique genes that drive oncogenic processes in human cancers. Serine protease 27 (PRSS27) has been recently defined as a possible driver gene in esophageal squamous cell carcinoma. However, no thorough pan-cancer study has been performed to date, including breast cancer. Methods: Using the TCGA (The Cancer Genome Atlas), the GEO (Gene Expression Omnibus) dataset, and multiple bioinformatic tools, we investigated the function of PRSS27 in 33 tumor types. In addition, prognosis analysis of PRSS27 in breast cancer was carried out, as well as in vitro experiments to verify its role as an oncogene. We first explored the expression of PRSS27 in over 10 tumors and then we looked into PRSS27 genomic mutations. Results: We discovered that PRSS27 has prognostic significance in breast cancer and other cancers' survival, and we developed a breast cancer prognostic prediction model by combining a defined set of clinical factors. Besides, we confirmed PRSS27 as an oncogene in breast cancer using some primary in vitro experiments. Conclusion: Our pan-cancer survey has comprehensively reviewed the oncogenic function of PRSS27 in various human malignancies, suggesting that it may be a promising prognostic biomarker and tumor therapeutic target in breast cancer.
Keywords: prognostic